1993
DOI: 10.1111/j.1095-8312.1993.tb00883.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological adaptations and plasticity of radular teeth of the Sacoglossa (= Ascoglossa) (Mollusca: Opisthobranchia) in relation to their food plants

Abstract: The radular teeth of 55 species of Sacoglossa (= Ascoglossa) (Mollusca: Opisthobranchia) with known diets are classified into three basic groups: triangular, blade‐shaped and sabot‐shaped. Cell wall composition of the food plant is the single most important factor influencing radular morphology. The algae eaten by sacoglossans have either xylan, mannan or cellulose as their structural wall component. Sabot‐shaped teeth are associated with diets of Siphonocladales and Cladophorales, which have cellulose cell wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 15 publications
2
66
1
Order By: Relevance
“…E. viridis feeds by piercing and sucking the cytoplasm from algal cells, and differences in the cell wall chemistry of the algal diets or the tooth morphology of the slugs could potentially constrain E. viridis switching to new hosts [23]. Previous studies have found variation in tooth morphology in different populations of E. viridis residing on different algal species [23], [36]. Slugs from Danish populations residing on Chaetomorpha linum possessed narrower and shorter teeth compared to French and English slugs found on C. fragile [23], [36].…”
Section: Discussionmentioning
confidence: 99%
“…E. viridis feeds by piercing and sucking the cytoplasm from algal cells, and differences in the cell wall chemistry of the algal diets or the tooth morphology of the slugs could potentially constrain E. viridis switching to new hosts [23]. Previous studies have found variation in tooth morphology in different populations of E. viridis residing on different algal species [23], [36]. Slugs from Danish populations residing on Chaetomorpha linum possessed narrower and shorter teeth compared to French and English slugs found on C. fragile [23], [36].…”
Section: Discussionmentioning
confidence: 99%
“…Although this has not been tested for sea hares, it has been shown that diet can influence tooth morphology (size and number) in other ''opisthobranch'' sea slugs. For example, in sacoglossans, smooth teeth can be associated with filamentous food (Bleakney 1990;Jensen 1993). Bleakney (1989) also noted some other morphological differences in the teeth of a species of ''opisthobranchs'' from different geographic regions.…”
Section: Discussionmentioning
confidence: 99%
“…We selected one such seaweed, H. incrassata, to study, because it is (i) colonized by the sacoglossan sea slug Elysia (16); (ii) well described in terms of its chemical defenses (14); (iii) the dominant seaweed within seagrass habitats throughout both the Florida Keys reef tract (11) and the wider Caribbean (12); and (iv) critical to the ecology of (13) and carbonate cycling within (12) Caribbean seagrass ecosystems. We studied Elysia because it (i) is thought to be a specialist, presumably associating with and feeding on Halimeda species (16,17,19,21,25); (ii) has been studied previously with regard to its sequestration of seaweed chloroplasts (34) and chemical defenses (19); and (iii) is the most abundant and widespread sacoglossan in the Florida Keys, which harbors the highest densities of sacoglossans in the Caribbean (35). Organisms were collected in the immediate vicinity of Pickles Reef and Rodriguez Key.…”
Section: Methodsmentioning
confidence: 99%
“…However, the sea slug Elysia tuca (hereafter Elysia) tolerates these defenses and selectively associates with and feeds on chemically rich species of green seaweed including H. incrassata (16). Elysia pierces the calcified thallus of its prey with a modified radula (17) and then feeds suctorially (18). It performs pharyngeal regurgitation while feeding to reduce the viscosity and facilitate withdrawal of cytoplasm (18).…”
mentioning
confidence: 99%